HUBUNGAN RELIGIUSITAS DENGAN KESEJAHTERAAN PSIKOLOGIS PADA PASIEN DIABETES MELITUS DI KLINIK HUSADA KIMIA FARMA SARIO MANADO - Bidjuni, Hendro; Kallo, Vandri; Saring, Hidayati Ratriyo (JURNAL KEPERAWATAN, 2019)
Abstract : Psychological Well-being is a full achievement of one's psychological potential and a situation when individuals can accept their own strengths and weaknesses as they are, have life goals, develop positive relationships with others, become independent individuals, able to control the environment, and continue to grow personally . The Purpose of this study was to find out whether there was a correlation between religiosity and psychological well-being in patients with diabetes mellitus at the Husada Kimia Farma Sario Manado Clinic. Samples were taken by purposive sampling technique that is as many as 70 people who meet the inclusion criteria. The research design used was a cross sectional study and data collected from respondents used a religiosity questionnaire and psychological well-being. The results of the Spearman Rho statistical test obtained a correlation coefficient of 0.570 (with a value of p = 0,000) which means the value of p <α (0.05). Conclution of this research hypothesis was accepted, this shows that there’s a correlation between religiosity and psychological well-being in patients with diabetes mellitus at the Husada Kimia Farma Sario Manado Clinic. Keywords : Religiosity, Psychological Well-Being, Diabetes Mellitus PatientsAbstrak : Kesejahteraan Psikologis ialah sebuah pencapaian penuh dari potensi psikologis seseorang dan suatu keadaan ketika individu dapat menerima kekuatan dan kelemahan diri apa adanya, memiliki tujuan hidup, mengembangkan relasi yang positif dengan orang lain, menjadi pribadi yang mandiri, mampu mengendalikan lingkungan, dan terus bertumbuh secara personal. Tujuan penelitian ini adalah untuk mengetahui apakah ada hubungan religiusitas dengan kesejahteraan psikologis pada penderita diabetes mellitus di klinik husada kimia farma sario manado. Sampel diambil dengan teknik pengambilan purposive sampling yaitu sebanyak 70 orang yang memenuhi kriteria inklusi. Desain Penelitian yang digunakan adalah cross sectional study dan data dikumpulkan dari responden menggunakan kuesioner religiusitas dan kesejahteraan psikologis. Hasil Penelitian uji statistik Spearman Rho diperoleh koefisien korelasi sebesar 0,570 (dengan nilai p= 0,000) yang berarti nilai p < α (0,05). Kesimpulan bahwa hipotesis penelitian diterima, hal ini menunjukkan bahwa ada hubungan antara religiusitas dengan kesejahteraan psikologis pada pasien dengan diabetes mellitus di Klinik Husada Kimia Farma Sario Manado.Kata Kunci : Religiusitas, Kesejahteraan Psikologis, Pasien Diabetes Mellitus